STUDENTS’ LANGUAGE ATTITTUDE AND READING INTEREST TOWARD ENGLISH AS FOREIGN LANGUAGE - Dadun Abdul Kohar; Leli Rahmawati (Universitas Kuningan, 2023)
Abstract: The EFL teaching and learning need to accommodate the findings, data, and information relating to language attitudes since it has a significant contribution to students’ motivation to learn English. A positive attitude toward English will be helpful in determining learning materials and increasing motivation in learning the language. One way to make students' attitudes towards English become positive is the use of ICT in language learning. Moreover, it is crucial to enhance their reading interest. This descriptive qualitative research focused on identifying the extent to which ICT in online reading classes could influence students' attitudes towards English learning and their reading interests. This study took data using observation, interview techniques, and questionnaires. Observations were carried out when the teaching-learning was being processed, while interviews were carried out with the teacher and her five students in grade 8. The questionnaire was delivered to 32 students through Google form when the online ICT-based reading teaching learning was completed. In this study, the researcher found that the teacher had carried out the teaching steps related to the curriculum 2013, besides the teacher used ICT in the process of teaching reading online. The results of interviews with the respondents also showed that ICT enhanced their attitudes toward English and it motivated them to write freely. Furthermore, the result of the questionnaire showed that their reading interest also increased.Keywords: Positive attitude towards EFL; online ICT-based reading class; reading